Electrical Treeing Properties Of Silicone Rubber/Organo Montmorillonite Nanocomposites As An Insulator For High Voltage Applications - Abd Jamil, Abdul Azim (2015)
Electrical phenomenon that occurred in polymeric insulating material prior to the insulation failure is considered as an electrical treeing. Electrical treeing can bring adverse effect on the reliability of electrical apparatuses and it mostly occurred for high voltage cable. Normally, nanofiller were used to retard the electrical treeing, therefore, organo-montmorillonite (OMMT) was chosen as the inhibitors to study the electrical treeing phenomenon. The knowledge on OMMT in the electrical properties field of high voltage insulations is insufficient although it has been proven excellent in other fields. OMMT was mixed with silicone rubber (SiR) which is another well-known material that has been used as polymeric insulating material. The performance of OMMT in SiR to retard electrical treeing was investigated by measuring four parameters which are treeing initiation voltage (TIV), treeing breakdown time (TBT), treeing propagation length (TPL) and electrical treeing growth rate. This performance of OMMT in SiR was compared with unfilled silicone rubber and SiR/SiO2 nanocomposites. Morphological analysis was conducted on samples of SiR/OMMT nanocomposites and SiR/SiO2 nanocomposites by using TEM, FESEM and FTIR. Results from the experiment revealed that the performance of SiR/OMMT nanocomposites were excellent than the unfilled SiR and SiR/SiO2 nanocomposites, plus the OMMT with 5wt% of in SiR recorded excellent results. Another interesting finding in this research was the OMMT layered silicate structure caused SiR to increase electrical properties and inhibit the growth of electrical treeing. Findings and results from the experiments are very useful for researchers in high voltage field in order to clarify the potential of using SiR/OMMT nanocomposites as polymeric insulating material in high voltage application